2007
DOI: 10.1159/000106782
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Prevents Early Steps of the Development of Diabetic Nephropathy in Rats

Abstract: Background/Aims: Recent studies suggested the involvement of the Akt/mammalian target of rapamycin (mTOR) pathway in the pathogenesis of diabetic nephropathy. The effect of mTOR blockade by rapamycin in diabetic nephropathy was investigated, but in vivo study of rapamycin treatment in the course of early diabetes is still insufficient. This study was designed to determine the therapeutic effects of rapamycin on diabetic nephropathy at an early stage. Methods: Diabetes was induced in Sprague-Dawley rats with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
123
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(125 citation statements)
references
References 60 publications
2
123
0
Order By: Relevance
“…However, there are hints that this regulatory pathway could be active in a less homeostatic relationship. Both enhanced mTOR activity (38,44) and increased GLUT1 expression (15) have been implicated in the pathogenesis of diabetic complications, especially nephropathy. Since upregulation of mTOR leads to enhanced GLUT1 expression, it is possible that mTOR plays a pathogenic role by stimulating GLUT1 expression and glucose uptake into susceptible glomerular cells in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are hints that this regulatory pathway could be active in a less homeostatic relationship. Both enhanced mTOR activity (38,44) and increased GLUT1 expression (15) have been implicated in the pathogenesis of diabetic complications, especially nephropathy. Since upregulation of mTOR leads to enhanced GLUT1 expression, it is possible that mTOR plays a pathogenic role by stimulating GLUT1 expression and glucose uptake into susceptible glomerular cells in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…This may have contributed to the renoprotection observed with rapamycin treatment. With regard to their primary mode of pharmacological action (10,30), mTOR inhibitors pose no direct effect on blood pressure. Therefore, it is likely that the lower blood pressure with rapamycin in this study was mediated indirectly through less renal damage and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ceramide(d18:0/16:0), ceramide monohexoside(d18:1/15:0), SM(d16:1/18:0), and SM(d18:1/18:0) were reversed by rapamycin. The previous study showed that ceramide increase in diabetic kidney and decrease after rapamycin treatment and the long established relationship of ceramide and apoptosis support ceramide as a reasonable biomarker candidate [141]. Streptozotocin significantly increased synthesis of many sphingolipids that was inhibited by rapamycin.…”
Section: Effect Of Dnmentioning
confidence: 96%